Current Stabilisation of Lithium Polymer Electric Vehicle Battery Using Fuzzy Logic Control - Imron, Arizal Mujibtamala Nanda; Utomo, Satryo Budi; Darmawan, Dimas Aldy; Kaloko, Bambang Sri (Jurnal Teknologi Informasi dan Terapan, 2024)
Renewable energy in electric vehicles (EVs) is crucial and requires careful consideration. To determine the initial capacity of lithium polymer batteries used in electric vehicles development, the batteries must be tested under various load and discharge conditions. The issue is that an increase in the level of load typically results in a corresponding decrease in battery lifespan. To extend the operational lifespan of the battery, it is necessary to conduct a variety of loading tests. These procedures involve monitoring battery voltage, current, and temperature during discharge with a 5-watt lamp load. The results of the study demonstrate that fuzzy control is an effective method to minimize the increase in battery temperature by stabilizing the current used by the battery. The fuzzy control system effectively regulates the battery with a capacity of 3300 mAh and a voltage of 11.1 Volts, maintaining a stable current of 0.3 A from the 3rd minute until the battery reaches its maximum capacity at 63 minutes. Fuzzy control delays the battery's temperature rise by approximately 14 minutes compared to a system without it. Temperature rise significantly affects the discharge speed of lithium polymer batteries